Oxidative stress-induced disruption of epithelial and endothelial tight junctions - Rao, Radhakrishna (Frontiers in bioscience, 2008)
Mounting body of evidence indicates that the disruption of epithelial tight junctions and resulting loss of barrier function play a crucial role in the pathogenesis of a variety of gastrointestinal, hepatic, pulmonary, kidney and ocular diseases. Increased production of inflammatory mediators such as cytokines and reactive oxygen species disrupt the epithelial and endothelial barrier function by destabilizing tight junctions. Oxidative stress induced by various reactive oxygen species such as hydrogen peroxide, nitric oxide, peroxynitrite and hypochlorous acid disrupt the epithelial and endothelial tight junctions in various tissues. The mechanism involved in oxidative stress-induced disruption of tight junction includes protein modification such as thiol oxidation, phosphorylation, nitration and carbonylation. The role of signaling molecules such as protein kinases and protein phosphatases in regulation of tight junctions is discussed in this article. Understanding such mechanisms in oxidative stress-induced disruption of epithelial and endothelial barrier functions is likely to provide insight into the pathogenesis of various inflammatory diseases, and may form a basis for the design of treatment strategies for different diseases.